Intraepithelial and lamina propria leucocyte subsets in inflammatory bowel disease: an immunohistochemical study of colon and rectal biopsy specimens. Issue 8 (August 1995) - Caballero, T; Nogueras, F; Medina, M T; Caracuel, M D; de Sola, C; Martínez-Salmerón, F J; Rodrigo, M; García del Moral, R
Abstract : AIMS–To gain new insights into the pathogenesis and differential diagnosis of ulcerative colitis and colonic Crohn's disease. METHODS–Immunohistochemistry for different leucocyte subsets was performed in biopsy specimens of the sigmoid colon and rectum from 55 patients with inflammatory bowel disease and 11 healthy controls. RESULTS–Colonic biopsy specimens from patients with active ulcerative colitis had significantly higher numbers of CD45+ and CD3+ leucocytes compared with those from patients with inactive disease, and higher numbers of total leucocytes and macrophages than those from patients with Crohn's disease. Rectal biopsy specimens from patients with Crohn's disease had greater numbers of intraepithelial leucocytes (CD45, CD3 and CD8 cells) than specimens from patients with active or inactive ulcerative colitis, or from healthy controls. CONCLUSIONS–Because of the phenotypic differences in the inflammatory infiltrate in the mucosa from the sigmoid colon and the rectum, the segment of the intestine to be biopsied should be specified. Assessment of the leucocytic component of the intraepithelial infiltrate in rectal biopsy specimens was more useful than examination of colonic biopsy specimens in the differential diagnosis of ulcerative colitis and Crohn's disease.